The first European Games – contrasting narratives - Giessen, Hans (Focus on events and narratives in language, psychology, social and medical practice, 2020)
The topic of my paper (i.e. the event I’m referring to) are the first European Games, held in June 2015 in Baku, Azerbaijan. These games, however, were not only the event that was an object of sports reporting but also reason to write and justify a narrative on the country and its political system. Interestingly, the narratives were indeed quite different, even when using the same terms. I would like to show this in a comparative study, using English language newspapers from the UK and from Ireland, as well as German language newspapers from Germany, Austria, and Luxembourg. Indeed, it seems to be the country of origin that determines how Azerbaijan’s political system is characterized, and not so much for example the political stance (for example, whether the very paper is to be found on the right – conservative – or on the left side of the political spectre). Also, the newspaper category does not seem to be decisive, that is, whether the very paper belongs to the group of the quality press or whether it belongs to the tabloids. Even if all newspapers of my corpus focus on the same event, i.e. the Baku games, and, more so, all of them even use the same linguistic terms and concepts (like Azerbaijan being characterized as “authoritarian”), characterization differs dramatically. The differences correlate only on the paper’s country of origin, and thus seem to depend on national narratives. Even in spite of using the same vocabulary, the stories are well opposed. For example, The Irish Times used the same (English language) concepts as the Guardian, but praised the games, whilst the Guardian denounced Azerbaijan’s political system to an extent that even its reporter is banned from Azerbaijan. Similarly, German and even more so Austrian papers deplore Azerbaijan’s political system, whilst the Luxemburg press praises the system for these well-organized games.